Ampharetidae (Annelida: Polychaeta) from Japan. Part II: Genera with elevated and modified notopodia - Imajima, Minoru; Reuscher, Michael G.; Fiege, Dieter (Zootaxa, 2013)
The second paper of the series about Ampharetidae from Japan includes twelve species of four genera with elevated and modified notopodia, Anobothrus Levinsen, 1884, Sosane Malmgren, 1866 (including species of the synonymized genera Muggoides Hartman, 1965, Sosanopsis Hessle, 1917, and Genus A sensu Uebelacker 1984), Tanseimaruana gen. nov., and Zatsepinia Jirkov, 1986. Tanseimaruana gen. nov. is related to Amphicteis Grube, 1850, but lacks prostomial glandular ridges and has a velum-like dermal outgrowth with two pairs of lobes across the dorsum of the first abdominal unciniger. The new genus comprises Tanseimaruana vestis comb. nov. (Hartman, 1965) (formerly Amphicteis vestis) and T. boninensis sp. nov. Seven additional new species, Anobothrus dayi sp. nov., A. fimbriatus sp. nov., A. flabelligerulus sp. nov., Sosane brevibranchiata sp. nov., Sosane trigintaduo sp. nov., S. uebelackerae sp. nov. (formerly Genus A sensu Uebelacker), and Zatsepinia jirkovi sp. nov., are described. Sosane cf. cinctus (Hartman, 1965), Sosane wireni (Hessle, 1917), and Zatsepinia rittichae Jirkov, 1986, all species previously known from the North Atlantic, are recorded from the North Pacific for the first time. A phylogenetic analysis of Sosane (including the synonymized genera Mugga Eliason, 1955, Muggoides, Sosanopsis, and Genus A sensu Uebelacker) suggests monophyly of the genus with Lysippe Malmgren, 1866 as sister taxon, and a monophyletic clade [Sosane cinctus, Sosane uebelackerae sp. nov., Mugga spp.] within Sosane. The monotypic genus Melinnata Hartman, 1965 has been found indeterminable.